Automotive and medical: can we learn from each other?. Issue 4 (23rd September 2011) - Kramer, Anne; Biró, Miklós; Messnarz, Richard; Palacios, Ricardo Colomo
SUMMARY In this paper, we present an analysis of the new standard ISO 26262 for the automotive industry. We compare this standard to existing regulations of another safety‐critical domain, that is, the medical device industry. As can be expected, a large number of activities coincide, because they simply correspond to common best practices that can also be found, for example, in ISO/IEC 15504. However, some interesting differences can be observed both in philosophy and in wording that make cross‐domain communication complicated. This paper is intended to encourage the exchange of experiences and methods between the two domains that are driven by the same concern, that is, the user's safety. We point out the most striking similarities and differences and translate from one domain to the other. Copyright © 2011 John Wiley & Sons, Ltd.